Pemanfaatan Teknologi Digital Wallet Sebagai Solusi Alternatif Pembayaran Modern: Literature Review - Fadhilah, Jihan; Layyinna, Cut Aja Anis; Khatami, Rijal; Fitroh, Fitroh (Journal of Computer Science and Engineering (JCSE), 2021)
Abstract: Financial technology innovation in the form of digital wallets is very interesting to the public. The efficiency offered from this payment system makes people start to switch from conventional payments to digital payments. In addition, many other factors influence multi-generational people using digital wallets as an alternative to their daily payments. The use of digital wallets is currently widely applied to online transportation transactions, purchases in e-commerce, to food and beverage delivery services. The method used in this study is a method of literature study with the goals to find out the development of digital wallet usage in the community from various journals sourced from Scopus and several websites that have been analyzed and processed by researchers into a literature review study. From the results obtained, it can be concluded that from year to year there is an increase in the number of digital wallet users, especially in Indonesia. Moreover after the Covid-19 pandemic, the number of digital wallet users is increasing because people have to avoid physical contact so that more transactions with digitally.Abstrak: Inovasi teknologi keuangan berupa digital wallet sangat manarik perhatian masyarakat. Efisiensi yang ditawarkan dari sistem pembayaran ini membuat masyarakat mulai beralih dari pembayaran konvensional ke pembayaran digital. Selain itu banyak faktor lain yang mempengaruhi para multi generasi menggunakan digital wallet sebagai alternatif pembayaran sehari-hari mereka. Penggunaan digital wallet saat ini banyak diterapkan untuk transaksi transportasi online, pembelian di e-commerce, hingga jasa pesan antar makanan dan minuman. Metode yang digunakan pada penelitian ini yaitu metode studi literatur dengan tujuan untuk mengetahui perkembangan penggunaan digital wallet di masyarakat dari berbagai jurnal yang bersumber dari Scopus dan beberapa website yang telah dianalisis dan diolah peneliti menjadi sebuah kajian literature review. Dari hasil yang didapatkan dapat disimpulkan bahwa dari tahun ke tahun terjadi peningkatan jumlah pengguna digital wallet, khususnya di Indonesia. Apalagi setelah pandemi Covid-19, jumlah pengguna digital wallet semakin meningkat karena masyarakat harus menghindari kontak fisik sehingga lebih banyak melakukan transaksi secara digital.